NSCAs Performance Training Journal - Sports Nutrition - special issue (NSCAs Performance Training Journal, 2008)
Learning from Olympians: Suzie Tuffey Riewald As an athlete, you were undoubtedly one of the 4 billion people that watched the recent Olympic Games in Beijing. This article takes a look at some of the outstanding performances of the '08 Olympics, and how proper mental skills played into the performances.